2013
DOI: 10.1136/thoraxjnl-2012-202646
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional assessment and tailored interventions for COPD: respiratory utopia or common sense?

Abstract: IntroductionThe rising disease burden from chronic obstructive pulmonary disease (COPD) requires new approaches.MethodWe suggest an approach based around three elements: inflammometry and multidimensional assessment to identify therapeutic targets and case management to design and implement an individualised treatment programme based on these assessments.DiscussionThis tailored approach to treatment would maximise efficacy, limit cost and permit a better risk–benefit ratio of treatment. The advantages include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 26 publications
3
130
0
4
Order By: Relevance
“…Also, in COPD a treatment strategy aimed to minimize eosinophilic inflammation and symptoms results in a significant reduction of exacerbations that require hospitalization, mainly in patients with COPD and eosinophilic airway inflammation at baseline (>3% sputum eosinophils) and sometimes requiring long-term oral corticosteroids. No difference was seen for milder exacerbations that require general practitioner visits only [McDonald et al 2013;Siva et al 2007]. Since eosinophilic inflammation has not been repeatedly shown as a distinguisher of ACOS compared with COPD and asthma alone, treatment aimed to reduce eosinophilic inflammation should therefore be performed in patients with proven eosinophilic inflammation instead of in groups assumed to have eosinophilic inflammation.…”
Section: Response To (Inhaled) Corticosteroidsmentioning
confidence: 99%
“…Also, in COPD a treatment strategy aimed to minimize eosinophilic inflammation and symptoms results in a significant reduction of exacerbations that require hospitalization, mainly in patients with COPD and eosinophilic airway inflammation at baseline (>3% sputum eosinophils) and sometimes requiring long-term oral corticosteroids. No difference was seen for milder exacerbations that require general practitioner visits only [McDonald et al 2013;Siva et al 2007]. Since eosinophilic inflammation has not been repeatedly shown as a distinguisher of ACOS compared with COPD and asthma alone, treatment aimed to reduce eosinophilic inflammation should therefore be performed in patients with proven eosinophilic inflammation instead of in groups assumed to have eosinophilic inflammation.…”
Section: Response To (Inhaled) Corticosteroidsmentioning
confidence: 99%
“…These traits should therefore be only viewed as a first step in this debate [62,63]. However, there is evidence that focusing on treatable traits in a multidimensional management plan leads to highly significant improvements in quality of life [60]. In addition, this approach may allow engagement of the patient in the goals of a treatment plan [64].…”
Section: Precision Medicine Of Chronic Airway Diseases: Why?mentioning
confidence: 99%
“…Some studies demonstrate that patients with COPD and eosinophilic inflammation treated with ICS present a significant improvement in bronchial inflammation together with clinical and spirometric improvement [36,37]. Two small, randomised trials have demonstrated that prescribing corticosteroids (oral or inhaled) according to the intensity of bronchial eosinophilic inflammation in patients with COPD was significantly superior in preventing exacerbations and improving health-related quality of life compared with the prescription of ICS according to current guidelines [38,39]. Already in 2007 the Canadian guidelines specified that: "if the asthma component (in COPD) is prominent, earlier introduction of ICS may be justified" [40].…”
Section: Treatmentmentioning
confidence: 99%